(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The study was done to evaluate the quality status of selected commercial brands of juices and jams based on laboratory analysis and public perception. The entire research work was carried out in two phases to evaluate the quality of juices and jams, available in local market. In phase I, a comprehensive baseline survey was done to know the public perception and this revealed that, according to the notion of most respondents, commercial juice and jam products available in market were adulterated by harmful food colors, low grade fruits and harmful preservatives and these were harmful for health. Besides, some outcome from this survey, such as, avoiding low quality products and adopting BSTI standard, enforcing law and imposing punishment and social motivation of food consumers to prevent adulteration. In phase II, chemical analysis and sensory evaluation of selected samples were done. The collected samples were four different brands of mango juices, two different brands of mango jam, two different brands of pineapple jam and apple jam from one brand. Different parameters of collected samples like moisture content, ash content, total soluble solid content, pH, acidity as citric acid, total plate count, yeast and mold count, preservative (Sulphur dioxide and Sodium benzoate) content and heavy metal (As, Pb, Cu, Zn and Sn) content were analyzed. Heavy metal content in every sample was below the detection level. Microbial load was in safe level according to gulf standard. However, preservative content in few samples was quite higher than acceptable limit. Other parameters of collected samples were in acceptable limits. Sensory evaluation showed that all commercial jam and juice samples were more or less equally acceptable and all products obtained satisfactory total score from sensory evaluation. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21410 J. Bangladesh Agril. Univ. 12(1): 183-188, June 2014